Higher education choice-making in the United States: freedom, inequality, legitimation - J. Dougherty, K (Centre for Global Higher Education, University of Oxford, 2018)
Professor Kevin J. Dougherty from Columbia University shows that the provision of many choices in higher education, widely seen as desirable and fair, reproduces and legitimates social inequality when those choices are not accompanied by enough information.